The Novice GT Researcher - Barney G. Glaser (Grounded Theory Review: An International Journal, 2009)
Make no mistake, as I said in my article, “The Future of Grounded Theory” (Qualitative Health Research, Nov, 1999) is in the hands of the beginning PhD researcher. I said “Unformed researchers embrace grounded theory for dissertation or master’s theses when, in their view, the more preconceived methods do not give relevant answers. Unformed researchers who can choose their own methods do so at the discretion of their advisers. The principal GT users today, mostly students who are doing MA and PhD theses or dissertations, are well into their academic careers and looking for methodologies that will result in data and theories relevant to what is going on in their research area of interest. This makes grounded theory very appealing on that one point alone — relevance.”